Factors influencing the decision of older adults to be assessed for transcatheter aortic valve implantation: An exploratory study. (1st December 2016) - Lauck, Sandra B; Baumbusch, Jennifer; Achtem, Leslie; Forman, Jacqueline M; Carroll, Sandra L; Cheung, Anson; Ye, Jian; Wood, David A; Webb, John G
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is the recommended therapy for patients with severe symptomatic aortic stenosis at increased surgical risk and likely to derive benefit. Multimodality and multidisciplinary assessment is required for the heart team to determine eligibility for TAVI in a primarily older population. Little is known about patients' motivation and perspectives on making the decision to undergo the complex assessment. Aims: To explore factors influencing patients' decision making to undergo TAVI eligibility assessment to inform practice, programme development, health policy and future research. Methods: An exploratory qualitative approach was used. Semistructured interviews were conducted with 15 patients at the time of their referral for assessment to a quaternary cardiac and high volume TAVI centre. Results: Multiple, intersecting factors that included biomedical, functional, social and environmental considerations influenced patients' decision. The six distinct factors were symptom burden, participants' perception as 'experienced' patients, expectations of benefit and risks, healthcare system and informal support, logistical barriers and facilitators, and obligations and responsibilities. Conclusions: The decision to undergo TAVI eligibility assessment is multifaceted and complex. Programmatic processes of care must be in place to facilitate appropriate and patient-centered decision making and access to TAVI. Strategies are required to mitigate the risks associated with the rapid deterioration of severe aortic stenosis, address patient and referring physicians' education needs, and provide individualised care and equitable access. Future research must focus on patients' experiences throughout the trajectory of TAVI care.